Clean is nourished: The links between WASH and nutrition - Yosef, Sivan (International Food Policy Research Institute, 2016)
MORE THAN 660 million people lack access to an improved water source and 2.4 billion people lack access to improved sanitation. Growing awareness of the global challenge we face in improving water, sanitation, and hygiene, widely known as WASH, has gained the problem a prominent place on global nutrition and health agendas. And an expanding body of research points to the great potential of WASH, as a set of interventions, to improve nutrition and health. For example, systematic reviews have shown that improving water quality can reduce the risk of diarrhea by 17 percent; and introducing hand hygiene interventions can reduce gastrointestinal by 31 percent and respiratory illness by 21 percent